MENTAL HEALTH SCREENING OF UKRAINIAN STUDENTS DURING THE WARTIME - Polyvianaia , Maryna (Collection of scientific papers «ΛΌГOΣ», 2024)
One of the problems that arose as a result of russia's military aggression against Ukraine is the deterioration of the mental health of the population, including a significant increase in the number of mental disorders among student youth [1-3].